Peran Fintech Syariah Dalam Meningkatkan Inklusi Keuangan - Sumarni Sumarni; Rika Rika; Nurul Waqia; Amanda Julianty; Akbar M. Sunusi (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2026)
The development of Islamic financial technology (sharia fintech) has become an important instrument in promoting financial inclusion in Indonesia, particularly for unbanked communities and Micro, Small, and Medium Enterprises (MSMEs). This study aims to analyze the role of sharia fintech in enhancing digital financial inclusion and to identify the challenges in its implementation. This research employs a qualitative approach using a literature review of relevant national and international journal articles on sharia fintech and financial inclusion. The findings indicate that sharia fintech significantly contributes to expanding access to financial services through digital transaction convenience, service efficiency, and the application of transparent and equitable Islamic principles. However, the optimization of sharia fintech still faces several challenges, including low levels of Islamic financial literacy, limited digital infrastructure, and the need for stronger regulatory and supervisory frameworks. Therefore, collaboration among regulators, industry players, and the public is essential to ensure the sustainability of sharia fintech as a driver of inclusive and sustainable financial development